Implementasi Tugas Dan Fungsi Kantor Urusan Agama Dalam Meningkatkan Kualitas Pelayanan Kepada Masyarakat Di Kecamatan Kampar Kiri - Muhammad Iran Simbolon; Ahmad Rofii Harahap (EL-EMIR Institute, 2026)
The purpose of this study is to determine the implementation of the duties and functions of the Office of Religious Affairs (KUA) in providing services to the community and to what extent its implementation is in accordance with the regulations of the Minister of Religious Affairs (PMA). The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects were the head of the Office of Religious Affairs (KUA), employees of the Office of Religious Affairs (KUA), and the community who received services at the Office of Religious Affairs (KUA) of Kampar Kiri District. The results of the study indicate that the Office of Religious Affairs (KUA) of Kampar Kiri District has carried out most of its duties and functions as mandated in the PMA, including in terms of marriage registration services, religious life guidance, and religious administration services. However, several obstacles were still found such as limited human resources, inadequate facilities and infrastructure, and a lack of public understanding of service procedures. The conclusion of this study is that although the implementation of the duties and functions of the Religious Affairs Office (KUA) in Kampar Kiri District has generally been carried out in accordance with regulations, it is still necessary to improve the quality of service by strengthening employee capacity and providing outreach to the community.